Surgical Management of a Rare Alar Cleft: A Case Report - Damar Dita Kirana; Indri Lakhsmi Putri; Mirnasari Amirsyah (Syntax Literate, 2026)
Alar cleft is a rare congenital nasal deformity affecting the nasal ala. It can be associated with craniofacial syndromes or isolated anomalies. Isolated congenital alar clefts are exceptionally uncommon, and only limited cases have been reported in the literature, making this condition a significant reconstructive challenge in pediatric patients. There are no criteria guiding the correction of congenital alar anomalies; therefore, surgical corrections might be challenging. A 3-month-old infant presented with an uncommon congenital alar cleft, leading to aesthetic concerns. We performed a surgical procedure by dividing the anterior and posterior flaps, trimming them, and connecting them with the nasal alar skin. This surgical technique is clinically important because it preserves native tissue, provides good vascularity and tissue alignment, minimizes visible scarring, and avoids the need for more complex grafting procedures. Postoperative follow-up showed significant improvement in nasal contour and symmetry; no complications such as wound dehiscence were reported. Various surgical techniques have been described for alar cleft repair. The choice of technique depends on the size and location of the defect, and surgeon experience. The chosen technique ensures good tissue alignment with minimal scarring. There are no specific techniques for repairing alar clefts. The goal of surgery is to achieve normal-like results. Early surgical intervention yields better outcomes, especially in psychological issues. This case also highlights the broader importance of individualized planning in pediatric reconstructive surgery, particularly in preserving facial growth, achieving long-term aesthetic outcomes, and improving quality of life in children with rare craniofacial anomalies.